2002
DOI: 10.1016/s0550-3213(02)00032-9
|View full text |Cite
|
Sign up to set email alerts
|

Minimal mixing of quarks and leptons in the SU(3) theory of flavour

Abstract: We argue that flavour mixing, both in the quark and lepton sector, follows the minimal mixing pattern, according to which the whole of this mixing is basically determined by the physical mass generation for the first family of fermions. So, in the chiral symmetry limit when the masses of the lightest (u and d) quarks vanish, all the quark mixing angles vanish. This minimal pattern is shown to fit extremely well the already established CKM matrix elements and to give fairly distinctive predictions for the as ye… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…It has been shown that these models are free from the EDM constraints and the off-diagonal phases lead to significant contribution to the observed CP violation in the kaon system, in particular to ε ′ /ε [5]. Let us consider, for instance, the case of Hermitian and hierarchical quark mass matrices with three zeros [21] …”
Section: Susy Models With Hermitian Flavor Structurementioning
confidence: 99%
“…It has been shown that these models are free from the EDM constraints and the off-diagonal phases lead to significant contribution to the observed CP violation in the kaon system, in particular to ε ′ /ε [5]. Let us consider, for instance, the case of Hermitian and hierarchical quark mass matrices with three zeros [21] …”
Section: Susy Models With Hermitian Flavor Structurementioning
confidence: 99%
“…The proportionality condition (43) is not so easy to generate from an underlying symmetry beyond the SM, but it is possible to realise it in a local chiral SU(3) family symmetry model [30].…”
Section: Mass Matrix Ansätze and Texturementioning
confidence: 99%
“…3 Non-abelian SU(2) and SU(3) flavour symmetry groupshave also been considered, see for example Refs. [30,[40][41][42] for some recent examples. and obtain a realistic charged fermion spectrum in an SMG £ Uð1Þ f £ Uð1Þ f 0 model 4 [45].…”
Section: Origin Of Texturementioning
confidence: 99%
“…It is also desirable to get texture zeros with the help of flavor symmetries in a spirit of Refs. [18], [32], [66][67][68][69][70][71][72][73][74][75][76][77][78]. These and related issues will be addressed elsewhere.…”
Section: Discussionmentioning
confidence: 99%